Giardia sp. and Cryptosporidium sp. Infections in Primates in Fragmented and Undisturbed Forest in Western Uganda - Salzer, Johanna S.; Rwego, Innocent B.; Goldberg, Tony L.; Kuhlenschmidt, Mark S.; Gillespie, Thomas R. (Journal of Parasitology, 2007)
The molecular identification of species and genotypes of Giardia spp. infecting wild mammals represents the most reliable tool to understand the role played by these animals as reservoirs of cysts infectious for human and other animals. Of 139 fecal samples collected from fallow deer (Dama dama L.) hunted in a Natural Reserve of northern Italy, the prevalence of Giardia sp. was 11.5% (16 of 139 animals), and it was higher in fawns than in older animals. Fragments of the beta-giardin and triose phosphate isomerase (tpi) genes were successfully polymerase chain reaction amplified and sequenced from 8 isolates. No sequence variation was observed between isolates at the 2 genetic loci. Sequence and phylogenetic analyses identified a Giardia duodenalis subtype that clusters with assemblage A isolates and that shows homologies of 98 and 97% at the beta-giardin and tpi loci, respectively, compared with the A1 subtype. Because the G. duodenalis subtype found in fecal samples of fallow deer has never been detected previously, its role as a pathogen for humans and domestic animals is unknown, but, considering its genetic distinctiveness, it is likely to be low.